2023
DOI: 10.1177/20494637231190191
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of progressive muscle relaxation technique in reducing cancer-related pain among palliative care patients: A randomized controlled trial

Abstract: Purpose Cancer-related pain (CRP) is a common and distressing symptom experienced by many patients receiving palliative care. The purpose of this trial was to evaluate the effectiveness of the progressive muscle relaxation (PMR) technique in reducing CRP in patients receiving palliative care. Methods A total of 148 patients diagnosed with cancer and receiving palliative care were randomly allocated to either an intervention or control group. The intervention group received a 4-week daily course of PMR techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…The first hypothesis, namely that the PMR technique can be employed to reduce POP levels, has been corroborated. The findings of Anshasi et al 13 , are in accordance with the results of this study, which demonstrate that the PMR technique can significantly reduce the intensity of cancer-related pain in patients receiving palliative care, both immediately and one month after the intervention. The findings of another study indicated that the PMR technique is an effective method for alleviating pain and abdominal distension in patients who have undergone colonoscopy 28 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The first hypothesis, namely that the PMR technique can be employed to reduce POP levels, has been corroborated. The findings of Anshasi et al 13 , are in accordance with the results of this study, which demonstrate that the PMR technique can significantly reduce the intensity of cancer-related pain in patients receiving palliative care, both immediately and one month after the intervention. The findings of another study indicated that the PMR technique is an effective method for alleviating pain and abdominal distension in patients who have undergone colonoscopy 28 .…”
Section: Discussionsupporting
confidence: 92%
“…Progressive muscle relaxation (PMR) is the most readily accessible and prescribed technique for inducing physical and mental relaxation 12 . This technique is associated with breathing exercises and includes the tension and relaxation of different groups of skeletal muscles 13 . The relaxation that occurs during PMR has been shown to reduce anxiety, release muscle tension, regulate neuromuscular activity, and reduce various forms of pain sensation by blocking the transmission of pain stimuli and changing pain perception 12 .…”
Section: Introductionmentioning
confidence: 99%